Mean streak [large type] : a novel - Brown, Sandra, 1948- (Grand Central Publishing, 2014)
Dr. Emory Charbonneau, a pediatrician and marathon runner, disappears on a mountain road in North Carolina. When she regains consciousness, she finds herself the captive of a man whose violent past is so dark that he won't even tell her his name. She's determined to escape him and willing to take any risks necessary to survive. Unexpectedly, however, the two have a dangerous encounter with people who adhere to a code of justice all their own.